2003
DOI: 10.1007/s00464-002-8817-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic mesh cruroplasty for large paraesophageal hernias

Abstract: Early results suggest that prosthetic mesh cruroplasty may be effective in reducing recurrence after laparoscopic repair of large paraesophageal hernias, but long-term follow-up is required in all patients to determine the true incidence of anatomic recurrence and prosthetic erosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(67 citation statements)
references
References 11 publications
2
59
1
5
Order By: Relevance
“…16,24 We and others advocate the use of mesh reinforcement of hiatal hernia repair in order to decrease the hernia recurrence. 13,17,[36][37][38] The efficacy of PTFE reinforcement in hiatal herniorraphy has been demonstrated in a randomized trial. 13 Our current indication for mesh utilization is a hiatal defect greater than 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…16,24 We and others advocate the use of mesh reinforcement of hiatal hernia repair in order to decrease the hernia recurrence. 13,17,[36][37][38] The efficacy of PTFE reinforcement in hiatal herniorraphy has been demonstrated in a randomized trial. 13 Our current indication for mesh utilization is a hiatal defect greater than 5 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, other studies have already demonstrated that the use of mesh lowers the rates of recurrence, it is the possibility of complications what we have do pay attention to 1,4,7,8,9,12 . In our series with a long follow-up period, we found no complications related to the use of a mesh, even in those patients with recurrence.…”
Section: Frantzides and Carlsonmentioning
confidence: 95%
“…One topic, however, has gained increasing focus: the use of prosthetic reinforcement of the crural repair 1,3,4,7,8,9,15,20 . Several types of series, prospective non-randomized studies and prospective randomized studies were published or are underway, trying to answer: 1) does it decrease recurrence?…”
Section: Introductionmentioning
confidence: 99%
“…Others, however, use mesh in patients with intrathoracic gastric location and recurrences [18,19]. Many surgeons approximate cruses with sutures and lay mesh on cruses [17,20]. They advocate that by doing so mesh would be in less contact with esophagus.…”
Section: Discussionmentioning
confidence: 99%